ISLAM ALA IKLAN - Elis Z. Anis (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
The article asserts that media has an important role in forming the consumptive society and indonesia, as the largest Muslim populous country becomes the central commodity for a number of various products. Moreover, during the special events of religious rituals such as Ramadhan and Eidul Fithr, it is considered to be the best time for the producers in making special advertising of Ramadhan and Eidul Fithr. As the advertisement is made so attractive and persuasive in the sight of people, a lot of them were easily attracted by. The presence of such luring devil for the attracted viewers has spent huge amount of money through products advertisement. Therefore, the religious ceremonies could not be understood in its correct sense. Unsurprisingly, some religious events including fasting is no longer understood as an attempt to feel the same suffering of those who are hungry and thirsty, but used as a right opportunity to be a pious Muslim to have excessive spending on the reason of preparing the fast-breaking together.